A new condition to identify isotropic dielectric-magnetic materials displaying negative phase velocity - Depine, Ricardo Angel (2004)
A new condition for characterizing isotropic materials with negative phase velocity was derived. The equivalence between this condition and its predecessors was also studied. A linear isotropic dielectric-magnetic medium characterized by complex-valued relative permittivity and relative permeability scalars was also considered. The wave equation gives the square of the complex-valued refractive index.